2021
DOI: 10.1101/2021.02.23.432474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 causes brain inflammation and induces Lewy body formation in macaques

Abstract: SARS-CoV-2 may cause acute respiratory disease, but the infection can also initiate neurological symptoms. Here we show that SARS-CoV-2 infection causes brain inflammation in the macaque model. An increased metabolic activity in the pituitary gland of two macaques was observed by longitudinal positron emission tomography-computed tomography (PET-CT). Post-mortem analysis demonstrated infiltration of T-cells and activated microglia in the brain, and viral RNA was detected in brain tissues from one animal. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…The first three studies did not find evidence of the virus in the brain using PCR at 3, 4, 7, and 21 days after infection [27,70,83] (Table 3). A fourth and fifth study [44,78] found viral RNA in multiple brain regions at 28 or 35 days post infection, but in one of these studies, the PCR findings could not be verified by antibodies against the nuclear capsid antigen [78]. A sixth study [51] found evidence of virus RNA and nuclear capsid antigen in the brain, including the olfactory bulb, at 1, 4 and 7 days after nasal inoculation.…”
Section: When and How Does The Virus Reach The Brain?mentioning
confidence: 99%
“…The first three studies did not find evidence of the virus in the brain using PCR at 3, 4, 7, and 21 days after infection [27,70,83] (Table 3). A fourth and fifth study [44,78] found viral RNA in multiple brain regions at 28 or 35 days post infection, but in one of these studies, the PCR findings could not be verified by antibodies against the nuclear capsid antigen [78]. A sixth study [51] found evidence of virus RNA and nuclear capsid antigen in the brain, including the olfactory bulb, at 1, 4 and 7 days after nasal inoculation.…”
Section: When and How Does The Virus Reach The Brain?mentioning
confidence: 99%
“…Similar neurotropic viruses such as Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS-CoV-1) coronaviruses have been shown to trigger the formation of Lewy bodies which are present in a range of neurologic diseases including Parkinson’s dementia. In a post-mortem analysis of the brains of rhesus macaques infected with SARS-CoV-2 virus, in the midbrain region was infiltrated by T-lymphocytes, activated microglia and intracellular Lewy bodies [ 13 ]. Such observations might herald a higher proportion or severity of critical illness induced long-term cognitive impairment or accelerated dementia (Fig.…”
mentioning
confidence: 99%
“…Viral trans-synaptic progression has previously been demonstrated with other coronaviruses [13]. Both RNA and protein of the virus have been found in neurons of patients who died from severe SARS-CoV-2 [14] and accompanied T cell infiltration and microglial activation in euthanized macaques after apparent remission of COVID-19 [15]. Such neuroinflammation requires long-term follow-up, considering the known relationships of neuroinflammation with the onset and progression of neurological and psychiatric diseases.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%